Adaptive Assessment in Islamic Religious Education for Promoting Inclusive Learning in Junior High Schools for Students with Special Needs - Hasanah, Ilma; Sumarna, Elan; Anwar, Saepul (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
Assessment in Islamic Religious Education (Pendidikan Agama Islam/PAI) plays a pivotal role in supporting inclusive education for students with special needs in Special Junior High Schools (Sekolah Menengah Pertama Luar Biasa/SMP LB). Beyond measuring cognitive, affective, and psychomotor domains, PAI assessment functions as a foundational mechanism for designing and implementing individualized learning programs that accommodate diverse learner characteristics. Nevertheless, its implementation continues to face several challenges, including the limited availability of tactile learning media, the heterogeneity of students’ disabilities and learning needs, and the lack of systematic and comprehensive assessment documentation. This study aims to examine adaptive assessment practices in PAI from teachers’ perspectives, with particular attention to assessment planning, implementation strategies, and the utilization of assessment outcomes. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using triangulation techniques to ensure data credibility. The research participants consisted of three PAI teachers from two Special Junior High Schools, anonymized as School A and School B. Teacher 1 teaches at School A, while Teachers 2 and 3 are affiliated with School B. The findings indicate that teachers implement adaptive assessment practices through a variety of methods, including oral questioning, systematic observation, practical worship activities, and the use of both simple instructional tools and digital media. Assessment results are subsequently utilized for instructional evaluation, remedial planning, collaborative reflection among teachers, and communication with parents or guardians. These findings underscore the importance of enhancing access to appropriate tactile media, strengthening systematic assessment documentation, and providing continuous professional development for teachers. Such efforts are essential to ensure that PAI assessment effectively contributes to equitable, meaningful, and inclusive educational practices in special school contexts. Abstrak: Asesmen Pendidikan Agama Islam (PAI) memiliki peran penting dalam mendukung pendidikan inklusif bagi peserta didik berkebutuhan khusus di Sekolah Menengah Pertama Luar Biasa (SMP LB). Asesmen tidak hanya berfungsi menilai aspek kognitif, afektif, dan psikomotor, tetapi juga menjadi dasar dalam penyusunan program pembelajaran individual. Namun, implementasinya masih menghadapi berbagai kendala, antara lain keterbatasan media taktil, keragaman kondisi peserta didik, serta minimnya dokumentasi formal. Penelitian ini bertujuan menganalisis praktik adaptive assessment PAI dari perspektif guru, dengan fokus pada perencanaan, strategi asesmen, dan pemanfaatan hasil asesmen. Penelitian menggunakan pendekatan deskriptif kualitatif dengan desain studi kasus melalui wawancara, observasi, dan analisis dokumentasi, serta pengolahan data dengan teknik triangulasi sumber. Subjek penelitian ini adalah tiga guru PAI dari dua SMP LB yang disamarkan sebagai Sekolah A dan Sekolah B. Guru 1 mengajar di Sekolah A, sedangkan Guru 2 dan Guru 3 di Sekolah B. Penelitian ini mengkaji praktik asesmen adaptif PAI, mencakup perencanaan, pelaksanaan, dan pemanfaatan hasil bagi peserta didik berkebutuhan khusus. Hasil penelitian menunjukkan bahwa guru menerapkan asesmen adaptif melalui tanya jawab, observasi, praktik ibadah, serta pemanfaatan media sederhana maupun digital. Hasil asesmen dimanfaatkan untuk evaluasi, remedial, kolaborasi antarguru, dan komunikasi dengan orang tua. Temuan ini menegaskan pentingnya penyediaan media taktil yang memadai, dokumentasi yang sistematis, serta pengembangan profesional guru secara berkelanjutan agar asesmen PAI dapat berkontribusi secara efektif terhadap pendidikan inklusif yang adil dan bermakna di sekolah luar biasa.